Efektivitas Program Tahta Keliling dalam Meningkatkan Kunjungan Pemustaka di UPT Perpustakaan Proklamator Bung Hatta - Aprilina, Sierly Ananta; Rahmah, Elva; Marlini, Marlini (TSAQOFAH, 2026)
The Tahta Keliling Program initiated by the Proklamator Bung Hatta Library Technical Implementation Unit (UPT) is a strategic effort to expand the reach of information services and enhance public access to reading materials, particularly for schools and communities located far from the main library. This study aimed to analyze the effectiveness of the Tahta Keliling Program in increasing library user visits by assessing program planning, implementation mechanisms, collection selection, operational constraints, and the impact of services on the intensity of visits to the library. A qualitative approach was employed using in-depth interviews with one program coordinator and four implementation staff members, supported by observation and activity documentation. The findings show that the Tahta Keliling Program has been planned and implemented systematically through route determination, collection selection, and flexible scheduling according to the needs of each location. The main challenges encountered include weather conditions, limited human resources, and supporting facilities; however, these were addressed through effective coordination, schedule adjustment, and proportional task distribution. Overall, the program has had a positive impact on increasing community interaction with the library and encouraging higher visit rates to the main library. This study concludes that the Tahta Keliling Program is effective in expanding access to literacy and increasing community participation in library services, and it holds potential as a reference model for developing sustainable mobile library services.